Impact of Surfactant Addition on Oxygen Mass Transfer in a Bubble Column. Issue 4 (April 2015) - McClure, Dale D.; Lee, Ai Chia; Kavanagh, John M.; Fletcher, David F.; Barton, Geoffrey W.
Abstract: The following text is an additional technical note for: Impact of Surfactant Addition on Oxygen Mass Transfer in a Bubble Column by Dale D. McClure, Ai Chia Lee, John M. Kavanagh, David F. Fletcher, and Geoffrey W. Barton Chem. Eng. Technol .2015, 38 (1), 44–52.DOI: 10.1002/ceat.201400403 .